Telling the Story of Jesus : Word—Communion—Mission - Tagle, Luis Antonio (Book collections on Project MUSE., 2015)
Three speeches by Cardinal Tagle of Manila. The first is about communion with other Christians and with the Trinity through Christ as the Word of God. The second is about Eucharistic adoration. The third presents evangelization as simply telling about Jesus, with a special focus on promoting Christianity in Asia.